Rate-regulated power control for supporting flexible transmission in future CDMA mobile networks. - Dongwoo Kim (IEEE Journal on selected areas in communications)
In code division multiple access (CDMA) mobile networks, transmitted power is controlled to provide each user an acceptable connection by limiting the interference seen by other users. Previous work has focused on finding a power assignment that maximizes the minimum carrier-to-interference ratio where the transmission rate of each user is known and fixed. In future mobile networks, however, fluctuations in mobiles' transmission rate should be considered in designing power control algorithms. In this work, we present an algorithm for controlling mobiles' transmitter power levels while explicitly handling their time-varying transmission rates. During the whole power control process, the required signal quality is always maintained. The traffic-carrying performance of the algorithm is evaluated by simulation where different types of users are sending burst data